Dynamics of epithelial–mesenchymal plasticity driving cancer drug resistance - Rashmi Bangarh; Reena V. Saini; Adesh K. Saini; Tejveer Singh; Hemant Joshi; Seema Ramniwas; Moyad Shahwan; Hardeep Singh Tuli (Cancer Pathogenesis and Therapy)
Epithelial–mesenchymal transition (EMT) promotes several cancers by increasing tumor cell motility, disrupting epithelial cell phenotypes, apical–basal polarity, and intracellular connections, and enhancing tumor resistance to immunotherapy and chemotherapy. Mesenchymal–epithelial transition (MET), the opposite of EMT, causes tumor metastasis. EMT drives primary tumor cells, whereas MET inhibits them. Importantly, the complex network of EMT includes cell–cell interactions in the tumor microenvironment. Transcription factors, post-translational regulation, cytokine-mediated signaling, and microRNAs control EMT. In this review, we discussed how molecular mechanisms, signaling networks, and epithelial/mesenchymal states affect cancer treatment resistance and the tumor microenvironment. Research on immunotherapy and chemotherapy problems associated with EMT suggests that targeting EMT might be a potential cancer treatment resistance strategy.